Technological Intentionality and Embodied Reconfiguration: A Phenomenological Reflection on AI-Enabled Ideological and Political Education (Journal of educational development exploration, 2026)
The rapid development of artificial intelligence technology is profoundly transforming the practical forms of ideological and political education in universities. From the perspective of technological phenomenology, AI is understood as an intentional intermediary that regulates the relationship between "human-technology-world." This study systematically examines its application effects in ideological and political education. The research reveals that AI not only injects momentum into precision ideological and political work, model innovation, and efficacy enhancement but also triggers three profound crises through its technological intentionality: the "mediation" of the educational subject-object relationship and the rupture of emotional bonds, the "superficialization" of value transmission and ideological risks, and the "technological dependence" of teacher-student subjectivity and the weakening of critical thinking. In response to these challenges, university ideological and political education must anchor its fundamental task of fostering virtue through nurturing, shifting from "tool empowerment" to "value coexistence," and striving to build a new ecological environment of "human-machine collaboration" in moral education, providing theoretical references and practical pathways for the high-quality development of ideological and political education in universities during the intelligent era.
Keywords: Technological phenomenology; Artificial intelligence; Ideological and political education; Technological intentionality; Embodiment